Network security and intrusion detection system - Rahman, Rajib; Zaman, Salman; Alam, Sarwar (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.